Ferrari’s separation from Fiat Chrysler Automobiles - Vaz, Mark Alexandre (2018)
The following case-study describes the circumstances surrounding Ferrari’s separation from Fiat Chrysler Automobiles (FCA). This paper’s structure is divided between the narrative and a teaching note. The case narrative describes all the events that result in Ferrari’s full separation from FCA and FCA’s recent most changes. The teaching note intends to analyse the possibility of investing in Ferrari’s IPO, the process of its separation and at the same time analysing FCA’s restructuring.